Chaotifying 2-D piecewise linear maps via a piecewise linear controller function - Elhadj, Z.; Sprott, J.C. (Нелінійні коливання, 2010)
A simple method for chaotifying piecewise linear maps of the plane using a piecewise linear controller function is given. A domain of chaosin the resulting controlled map was determined exactly and rigorously.